2021
DOI: 10.1002/admi.202100813
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite‐Type Oxynitride Nanofibers Performing Photocatalytic Oxygen and Hydrogen Generation

Abstract: Ba5Nb4O15 nanofibers with tailored nanofiber diameters are prepared via electrospinning, and treated in ammonia gas to synthesize niobate oxynitride nanofibers. Most importantly, the nanofibers retain their fiber morphology during ammonolysis, and the nanofiber diameter of the converted fibers can be adjusted. Only a thorough characterization, including detailed Rietveld refinements, can reveal that the ammonolysis of Ba5Nb4O15 results not only in BaNbO2N, but also generates Ba2NbO3N as additional oxynitride p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…48−50 The hydrophilicity/hydrophobicity of materials and the intermediates generated from water decomposition are highly related to the activity of photocatalytic reactions. 51,52 Therefore, we have explored water adsorption and its dissociation on the (100) and (001) surfaces of BaNbO 2 N. The adsorption energy (E ads ) of a water molecule on a surface is defined according to the following equation 11) where E total is the total energy of a water molecule supported on a surface, E surface is the energy of a relaxed clean surface, and E H 2 O is the energy of a water molecule in a supercell with the same size as the clean surface. According to the definition, a negative value of E ads means a thermodynamically favorable adsorption process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…48−50 The hydrophilicity/hydrophobicity of materials and the intermediates generated from water decomposition are highly related to the activity of photocatalytic reactions. 51,52 Therefore, we have explored water adsorption and its dissociation on the (100) and (001) surfaces of BaNbO 2 N. The adsorption energy (E ads ) of a water molecule on a surface is defined according to the following equation 11) where E total is the total energy of a water molecule supported on a surface, E surface is the energy of a relaxed clean surface, and E H 2 O is the energy of a water molecule in a supercell with the same size as the clean surface. According to the definition, a negative value of E ads means a thermodynamically favorable adsorption process.…”
Section: Resultsmentioning
confidence: 99%
“…The material could be applied in photocatalytic hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) by decorating with Pt or CoNbO 4 cocatalysts. 11 Kodera et al reported that the morphology of single-crystalline BaNbO 2 N particles can be tuned by the effect of different kinds of alkali halide flux treatments. 12 The experimental results by Seo BaNbO 2 N were highly dependent on the annealing temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also shows that a normalization to surface area is important for a correct interpretation of the photocatalytic activity of photocatalysts, which was already shown before. [29,[36][37][38] The TiO2 aerogels were all regained after the photocatalytic hydrogen experiments by washing and supercritical drying. XRD pattern after the photocatalytic hydrogen production experiments are shown in Figure S3.…”
Section: Photocatalytic Hydrogen Evolution and Electron Storagementioning
confidence: 98%
“…To date, a variety of semiconductor photocatalysts have been developed for achieving efficient O 2 evolution. 12,13 Among these photocatalysts, bismuth vanadate (BiVO 4 ) has attracted much attention because of its narrow band gap, good photostability, nontoxicity, and high oxygen evolution activity under visible light. 14−19 However, pure BiVO 4 is not suitable for hydrogen production since the conduction band position of BiVO 4 is very close to the reduction potential of H + /H 2 (0 V vs NHE at pH = 0).…”
Section: ■ Introductionmentioning
confidence: 99%